A Study on Field Current Ripple Reduction of Wound Field Synchronous Motor for EVs - Kang, Jun-Kyu; Lim, Hong-Sik; Kim, Ki-Chan (International Journal of Engineering and Technology, 2018)
Background/Objectives: Since the WFSM controls the field current by applying DC current to the field winding, it has the advantage that the magnetic flux of the rotor can be controlled. However, if the rotor of the WFSM rotates, the field current ripple occurs and it has an unfavorable influence on the motor control Methods/Statistical analysis: For the basic model, the maximum output is 80 kW. The WFSM compares the results of the motor performance test with the data values of the FEM simulation to analyze the causes of the current ripple. In addition, basic model and the design model applied the skew method is compared and analyzed by the finite element analysis method simulation. Findings: Looking at the waveform of the actually measured test data of WFSM, it is found that the field current ripple of 6 harmonic components per cycle with electrical angle occurs. This field current ripple affects the inverter current for driving the motor. As the electric motor rotates, the magnetic resistance in the air gap changes, which changes the inductance. The number of slot open each per rotor pole of the basic model is six. The inductance changes six times, and field current ripple of six harmonic components occurs based on this change. This was clarified through test and the FEM simulation. In order to reduce the six harmonics ripple of field currents, FEM analysis was performed by applying the skew method to the rotor. Each waveform is synthesized with phase difference in this skew method and the field current ripple of the 6th harmonic component decreases. Improvements/Applications: The skew method is used to analyze field current ripple through FEM analysis and characteristics are derived. Â